2021
DOI: 10.1101/2021.08.30.21262686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiovascular disease and all-cause mortality risk prediction from abdominal CT using deep learning

Abstract: Cardiovascular disease is the number one cause of mortality worldwide. Risk prediction can help incentivize lifestyle changes and inform targeted preventative treatment. In this work we explore utilizing a convolutional neural network (CNN) to predict cardiovascular disease risk from abdominal CT scans taken for routine CT colonography in otherwise healthy patients aged 50-65. We find that adding a variational autoencoder (VAE) to the CNN classifier improves its accuracy for five year survival prediction (AUC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Additionally, deep learning models can be used to predict future development cancer. The concept of care gap is that eventually patients do routine scans or MRI for other conditions and some AI models already have been developed to predict disease, for instance cardiovascular scores from CT scans [ 32 , 33 ]. A study reported on the ability to predict a 5-year future breast cancer risk from normal mammograms using deep-learning CNNs [ 34 ].…”
Section: Artificial Intelligence For Cancer Imagingmentioning
confidence: 99%
“…Additionally, deep learning models can be used to predict future development cancer. The concept of care gap is that eventually patients do routine scans or MRI for other conditions and some AI models already have been developed to predict disease, for instance cardiovascular scores from CT scans [ 32 , 33 ]. A study reported on the ability to predict a 5-year future breast cancer risk from normal mammograms using deep-learning CNNs [ 34 ].…”
Section: Artificial Intelligence For Cancer Imagingmentioning
confidence: 99%
“…In parallel, there have been efforts in related all-cause mortality prediction problems to include medical imaging data. Elton et al 5 have successfully explored using abdominal CT scans for cardiovascular disease and five-year survival prediction, similarly, in another work focused on CT imaging, Yan and colleagues 6 used low-dose CT imaging to predict all-cause mortality for lung cancer subjects. However, such imaging-focused approaches have not yet been explored for general body-composition-based allcause mortality prediction models.…”
Section: Plain Language Summarymentioning
confidence: 99%